Grain-refined atomized nickel-iron powder and method for producing the same

CN122955928APending Publication Date: 2026-10-23GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610886436.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

在湿法冶金从镍铁粉中提炼镍铁离子时,常规技术仅能通过提高温度、酸浓度来加快镍铁离子的提炼速率;其中,温度的升高伴随着高能耗,酸浓度的升高伴随着对设备的高腐蚀性,且目前获得的镍铁粉的酸溶速度无法达到生产需求

Benefits of technology

本发明提供的晶粒细化的雾化镍铁粉具有较低的平均晶粒尺寸,通过控制雾化镍铁粉平均晶粒尺寸,其在后续酸溶过程中具有良好的酸溶速率。本发明还提供了上述晶粒细化的雾化镍铁粉的制备方法,通过加入氧化铝作为晶粒细化剂,其具有较高的熔点,能稳定存在于高温混合熔体中,在进行水雾化时作为非均匀形核核心,起到钉扎作用,诱导混合熔体中的镍铁在凝固时形成大量晶核,晶粒被迫变小;在退火时,通过将含铝雾化镍铁粉加热并缓慢冷却,可促进再结晶和均匀化,使粗大晶粒转变为细小;同时,由于氧化铝预先分布在晶界上,可阻止晶界迁移,进一步抑制晶粒高温长大;在脱铝时,采用碱液可以溶解去除α型氧化铝,由于碱液中氧的存在,会对镍铁粉造成轻微氧化,产生大量结构缺陷,同时脱铝后的粉体颗粒更加疏松,真密度更低,越利于酸的溶解。通过二次退火还原,镍铁原子在缺陷处重新形核,再生成的晶粒更加细化,且又进行了内部晶粒的细化,最终获得比表面积大且晶粒尺寸较小的雾化镍铁粉。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955928A_ABST
    Figure CN122955928A_ABST
Patent Text Reader

Abstract

The application discloses a grain-refined atomized nickel-iron powder and a preparation method thereof, and relates to the technical field of metal powder. The grain-refined atomized nickel-iron powder has an average grain size D of 18-25 nm in the direction perpendicular to the measured crystal face, and the average grain size D is calculated by using the Scherrer formula D=. The grain-refined atomized nickel-iron powder has a small average grain size D, and thus has a good acid dissolution rate in the subsequent acid dissolution process. The preparation method provided by the application adds aluminum oxide as a grain-refining agent, and cooperates with high-pressure water atomization to induce a large number of crystal nuclei when nickel-iron solidifies in the mixed melt, so that the grain is forced to be thin; during annealing, the coarse grains are transformed into small ones, and the high-temperature growth of the grains is inhibited; during dealumination, the aluminum oxide is removed and a large number of structural defects are generated, and through secondary annealing reduction, nickel-iron atoms are re-nucleated at the defects, so that the grain refinement is further realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal powder technology, and more specifically, to a finely grained atomized nickel-iron powder and its preparation method. Background Technology

[0002] Nickel-iron alloy powder is a key intermediate in modern industry and is widely used in the production of stainless steel, special alloy steel, soft magnetic devices, new energy, precious metal recycling and other fields.

[0003] In the preparation of nickel-iron solutions using hydrometallurgy, efficient dissolution is fundamental for subsequent high-value utilization. Acid dissolution, as a mainstream hydrometallurgical technology, relies on the redox reactions between acid and nickel-iron powder to convert the metal into soluble ions. Compared to pyrometallurgical methods, it offers advantages such as operational flexibility, low energy consumption, and high selectivity. Furthermore, it allows for the selective application of iron in lithium iron phosphate cathode materials for new energy applications and nickel in lithium nickel cobalt manganese oxide cathode materials for new energy applications.

[0004] With increasing demand, there is a need to further improve production efficiency. In hydrometallurgical extraction of nickel-iron ions from nickel-iron powder, conventional technologies can only accelerate the extraction rate by increasing temperature and acid concentration. However, the increase in temperature is accompanied by high energy consumption, and the increase in acid concentration is accompanied by high corrosiveness to equipment. Moreover, the acid dissolution rate of the nickel-iron powder obtained at present cannot meet production requirements.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a finely grained atomized nickel-iron powder and its preparation method.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a finely grained atomized nickel-iron powder, wherein X-ray diffraction analysis shows that its average grain size D in the direction perpendicular to the measured crystal plane is 18-25 nm, and the average grain size D is expressed by the Scherrer formula D = calculate; K is the shape factor, a constant, and is set to 0.89; λ is the X-ray wavelength, λ = 0.15406 nm; β is the full width at half maximum (FWHM) of the diffraction peak, in radians; θ is the Bragg diffraction angle, expressed in degrees.

[0008] In an optional embodiment, the specific surface area S of the grain-refined atomized nickel-iron powder is 0.5-2.5 m². 2 / g; And / or, the true density ρ of the grain-refined atomized nickel-iron powder is 7.6-8.7 g / cm³. 3 .

[0009] In an optional embodiment, the powder activity H of the grain-refined atomized nickel-iron powder is... The powder activity H of the finely grained atomized nickel-iron powder is 7-22 m / g.

[0010] Secondly, the present invention provides a method for preparing atomized nickel-iron powder with refined grains as described in the foregoing embodiments, comprising: Alumina is added to molten nickel-iron and mixed thoroughly to obtain a mixed melt; The mixed melt is atomized by high-pressure water to obtain nickel-iron powder slurry; The nickel-iron powder slurry is subjected to magnetic separation, dehydration and drying to obtain aluminum-containing atomized nickel-iron powder; The aluminum-containing atomized nickel-iron powder is annealed and then placed in an alkaline solution to remove aluminum, resulting in a dealuminized intermediate powder. The dealuminated intermediate powder is subjected to magnetic separation, dehydration and drying to obtain dealuminated atomized nickel-iron powder; The dealuminated nickel-iron powder is subjected to secondary annealing to obtain atomized nickel-iron powder with refined grains.

[0011] In an optional embodiment, the alumina is α-type alumina with a particle size Dv50 of 0.1-2.0 μm; And / or, the mass ratio of the alumina to the molten nickel-iron is (200g-600g):1000kg.

[0012] In an optional embodiment, the annealing includes heating the aluminum-containing atomized nickel-iron powder to 450-550°C at a heating rate of 5-10°C / min under a hydrogen atmosphere, holding it at that temperature for 30-90min, and then cooling it to 180-220°C in the furnace. And / or, the dealuminization includes adding the annealed and furnace-cooled aluminum-containing atomized nickel-iron powder to an alkaline solution, introducing oxygen, and soaking it for 3-6 hours at a temperature of 180-220°C and a pressure of 1.5-3.5 MPa.

[0013] In an optional embodiment, the solid-liquid ratio of the aluminum-containing atomized nickel-iron powder to the alkaline solution is 500-800 g / L; And / or, the alkaline solution is a sodium hydroxide solution with a mass percentage concentration of 50%-70%; And / or, the oxygen partial pressure of the oxygen is 1.5-3.5 MPa.

[0014] In an optional embodiment, the present invention provides a method for preparing grain-refined atomized nickel-iron powder according to the foregoing embodiments, wherein the secondary annealing includes heating the dealuded atomized nickel-iron powder to 450-550°C at a heating rate of 5-10°C / min under a hydrogen atmosphere, holding it at that temperature for 30-90min, and then cooling it to room temperature in the furnace.

[0015] In an optional embodiment, the mixing includes rotating the molten nickel-iron and the alumina with electromagnetic stirring. The magnetic induction intensity of the electromagnetic stirring is 0.08-0.20T, the stirring frequency is 5-20Hz, the stirring time is 5-20min, and the stirring temperature is 1500℃-1600℃.

[0016] In an optional embodiment, during high-pressure water atomization, the flow rate of the mixed melt is 0.5-1.0 kg / s, the water pressure is 1-5 MPa, the water temperature is 40-60℃, and the water flow rate is 80-150 m / s. And / or, the high-pressure water atomization is performed using a coaxial annular slit nozzle, wherein the annular slit is the high-pressure water outlet and the inner hole is the melt outlet; the diameter of the melt outlet is 1.0-1.5mm, the slit of the high-pressure water outlet is 0.2-0.5mm, and the water and the melt flow form an impact angle of 40°-50°.

[0017] The present invention has the following beneficial effects: The atomized nickel-iron powder with refined grains provided by this invention has a low average grain size. By controlling the average grain size of the atomized nickel-iron powder, it exhibits a good acid dissolution rate during subsequent acid dissolution. This invention also provides a method for preparing the above-mentioned atomized nickel-iron powder with refined grains. By adding alumina as a grain refiner, which has a high melting point and can stably exist in a high-temperature mixed melt, it acts as a non-uniform nucleation core during water atomization, playing a pinning role and inducing the nickel-iron in the mixed melt to form a large number of crystal nuclei during solidification, forcing the grains to become smaller. During annealing, heating and slowly cooling the aluminum-containing atomized nickel-iron powder can promote recrystallization and homogenization, transforming coarse grains into fine grains. At the same time, since alumina is pre-distributed on the grain boundaries, it can prevent grain boundary migration, further inhibiting high-temperature grain growth. During dealuminization, an alkaline solution can be used to dissolve and remove α-alumina. Due to the presence of oxygen in the alkaline solution, it will cause slight oxidation of the nickel-iron powder, generating a large number of structural defects. At the same time, the powder particles after dealuminization are more porous and have a lower true density, which is more conducive to acid dissolution. Through secondary annealing and reduction, nickel-iron atoms re-nucleate at the defects, and the regenerated grains are more refined. Furthermore, the internal grains are refined, ultimately resulting in atomized nickel-iron powder with a large specific surface area and small grain size. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 The XRD pattern is from Example 2. Figure 2 The XRD pattern is from Example 3. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0021] This invention provides a finely grained atomized nickel-iron powder. X-ray diffraction analysis shows that its average grain size D, perpendicular to the measured crystal plane, is 18-25 nm. The average grain size D is calculated using the Scherrer formula: D = ... Calculate; where K is the shape factor, a constant, taken as 0.89; λ is the X-ray wavelength, λ=0.15406nm; β is the half-width at half maximum (FWHM) of the diffraction peak, in radians; θ is the Bragg diffraction angle, in degrees.

[0022] The atomized nickel-iron powder with refined grains in this invention has a small average grain size. Studies have shown that an average grain size within the above-mentioned range results in a good acid dissolution rate during the subsequent acid dissolution process.

[0023] Furthermore, this invention not only limits the average grain size D of the finely grained atomized nickel-iron powder, but also limits the specific surface area S of the finely grained atomized nickel-iron powder to be 0.5-2.5 m². 2 / g, and a true density ρ of 7.6-8.7g / cm³. 3 As can be seen, the present invention has a large specific surface area and a good acid dissolution rate in the subsequent acid dissolution process.

[0024] The term "average grain size D" refers to the average size of grains (single-crystal regions with essentially uniform internal crystallographic orientation) in polycrystalline materials. In this invention, it is characterized using the XRD Scherrer equation. "Specific surface area" refers to the total surface area per unit mass of material, including the external surface area and the internal surface area of ​​pores. "True density" refers to the density of a material including its internal closed pores, calculated as the material mass divided by the sum of the solid volume (the volume occupied by the solid framework) and the volume of the internal closed pores. "True density" can be measured using the gas displacement method.

[0025] This invention defines the average grain size D, specific surface area S, and true density ρ of atomized nickel-iron powder with refined grains. It can be seen that atomized nickel-iron powder with refined grains has a lower average grain size and a larger specific surface area, which ensures that the atomized nickel-iron powder with refined grains has more active sites, is more easily reacted, and has a good acid dissolution rate in the subsequent acid dissolution process; moreover, an appropriate true density can prolong the contact time between nickel-iron powder and acid solution, which can promote acid dissolution.

[0026] Furthermore, this invention also specifies the powder activity H= of the finely grained atomized nickel-iron powder. The powder activity of finely grained atomized nickel-iron powder was evaluated using three parameters: average grain size D, specific surface area S, and true density ρ. "Powder activity" refers to the ease with which metal powder undergoes oxidation, combination, sintering, and reaction dissolution under room temperature / heating conditions. In this invention, the powder activity H of the finely grained atomized nickel-iron powder is 7-22 m / g. A good acid dissolution effect is achieved when the specific surface area S, average grain size D, and true density ρ synergistically combine to meet the above powder activity value.

[0027] Furthermore, the present invention also provides a method for preparing atomized nickel-iron powder with refined grains, which includes the following steps: S1. Add aluminum oxide to the molten nickel-iron and mix well to obtain a mixed melt.

[0028] The nickel-iron molten liquid is obtained by melting nickel-iron alloy blocks from laterite nickel ore through pyrometallurgy. The mass ratio of nickel to iron can vary depending on the source of the laterite nickel ore. The total content of nickel and iron accounts for more than 95% (mass percentage) of the total metal content in the nickel-iron alloy block. The nickel-iron alloy block can be added to the furnace and melted to prepare the nickel-iron molten liquid.

[0029] Alumina is added to the molten nickel-iron, wherein the alumina is α-type alumina with a particle size Dv50 of 0.1-2.0 μm, and the mass ratio of alumina to molten nickel-iron is (200g-600g):1000kg. α-type alumina acts as a grain refiner, has a high melting point, and can exist stably in the high-temperature molten nickel-iron.

[0030] Uniform mixing is achieved by rotary electromagnetic stirring of molten nickel-iron and alumina, preventing alumina particles from agglomerating and becoming large particles that enter the slag phase. The rotary electromagnetic stirring operates at a magnetic induction intensity of 0.08-0.20T, a stirring frequency of 5-20Hz, a stirring time of 5-20min, and a stirring temperature of 1500℃-1600℃.

[0031] Wherein, the particle size Dv50 of alumina can be, for example, any one or a range between any two of 0.1μm, 0.3μm, 0.5μm, 0.8μm, 1.0μm, 1.3μm, 1.5μm, 1.8μm, and 2.0μm; the mass ratio of alumina to molten nickel-iron can be, for example, any one or a range between any two of 200g:1000kg, 300g:1000kg, 400g:1000kg, 500g:1000kg, and 600g:1000kg; the magnetic induction intensity of the rotary electromagnetic stirrer can be, for example, [missing information]. The stirring frequency can be, for example, any one or any two of 0.08T, 0.1T, 0.12T, 0.15T, 0.18T, and 0.20T; the stirring frequency can be, for example, any one or any two of 5Hz, 10Hz, 15Hz, and 20Hz; the stirring time can be, for example, any one or any two of 5min, 10min, 15min, and 20min; and the stirring temperature can be, for example, any one or any two of 1500℃, 1530℃, 1550℃, 1580℃, and 1600℃.

[0032] S2. The mixed melt is atomized by high-pressure water to obtain nickel-iron slurry.

[0033] "High-pressure water atomization" refers to an industrial powder-making process in which molten liquid metal is continuously dropped and subjected to direct and violent impact, shearing, and tearing by high-pressure, high-speed water flow, causing the liquid metal column to break into countless tiny metal droplets. The droplets are then rapidly cooled and solidified in the water, eventually becoming metal powder.

[0034] Specifically, in this invention, the flow rate of the mixed melt during high-pressure water atomization is 0.5-1.0 kg / s, the water pressure is 1-5 MPa, the water temperature is 40-60℃, and the water flow rate is 80-150 m / s.

[0035] There are various implementation methods for high-pressure water atomization. This invention provides a typical but non-limiting example in which high-pressure water atomization is performed using a coaxial annular slit nozzle, wherein the annular slit is the outlet for high-pressure water flow and the inner hole is the outlet for melt flow; the diameter of the melt flow outlet is 1.0-1.5 mm, the slit of the high-pressure water flow outlet is 0.2-0.5 mm, and the water and melt flow form an impact angle of 40°-50°.

[0036] In this invention, the impact angle between water and the melt is used to impact the melt, causing the mixed melt to be broken into countless tiny metal droplets. At the same time, during water atomization, because the mixed melt contains α-alumina, which acts as a non-uniform nucleation core, it induces the formation of a large number of crystal nuclei during solidification of the nickel-iron molten metal, forcing the grains to become finer.

[0037] S3. The nickel-iron powder slurry is subjected to magnetic separation, dehydration and drying to obtain aluminum-containing atomized nickel-iron powder.

[0038] Magnetic separation refers to the preliminary separation of nickel-iron powder slurry using a wet magnetic separator to obtain wet nickel-iron powder with a water content of 25%-30%. Since both nickel and iron are strongly ferromagnetic materials, after the mixed melt is atomized by high-pressure water to obtain nickel-iron powder slurry, the nickel-iron alloy particles as a whole are strongly magnetic. The wet magnetic separator can adsorb the nickel-iron powder in the nickel-iron powder slurry. However, the impurities mixed in during the melting, smelting, and powdering of nickel-iron are non-magnetic or weakly magnetic and are not easily adsorbed during magnetic separation. Magnetic separation can effectively remove impurities, control composition, stabilize grade, and reduce the content of harmful impurities.

[0039] Dehydration refers to the process of dehydrating the wet nickel-iron powder obtained by magnetic separation using a vacuum filter to obtain wet nickel-iron powder with a moisture content of 10%-15%; drying refers to drying at 100-120℃ to obtain aluminum-containing atomized nickel-iron powder.

[0040] S4. After annealing, aluminum-containing atomized nickel-iron powder is placed in an alkaline solution to remove aluminum, thus obtaining aluminized intermediate powder.

[0041] Annealing involves heating aluminum-containing atomized nickel-iron powder to 450-550°C at a heating rate of 5-10°C / min under a hydrogen atmosphere, holding at that temperature for 30-90 minutes, and then cooling it to 180-220°C in the furnace.

[0042] Because water atomization droplets solidify extremely rapidly, they generate significant thermal and structural stresses, leading to severe distortion within the powder particles. Therefore, this invention employs annealing after high-pressure water atomization. Annealing releases lattice distortion, relieves stress, reduces brittleness, and stabilizes the powder morphology. It also reduces excessive powder activity, inhibits spontaneous oxidation, spontaneous combustion, and corrosion, and refines or regularizes grains, achieving microstructural reconstruction. Furthermore, it improves magnetic properties.

[0043] In particular, during low-temperature annealing, the present invention promotes recrystallization and homogenization by heating and slowly cooling aluminum-containing atomized nickel-iron powder, thereby transforming coarse grains into fine grains; at the same time, since alumina is pre-distributed on the grain boundaries, it can prevent grain boundary migration and further suppress high-temperature grain growth.

[0044] Dealumination involves adding annealed and furnace-cooled atomized nickel-iron powder containing aluminum to an alkaline solution, while oxygen is introduced. The solution is then soaked for 3-6 hours at 180-220℃ and 1.5-3.5 MPa. During dealumination, the alkaline solution dissolves and removes α-alumina. The presence of oxygen in the alkaline solution causes slight oxidation of the nickel-iron powder, generating numerous structural defects. These defects enhance the dissolution and removal efficiency of the alkaline solution for α-alumina.

[0045] The solid-liquid ratio of aluminum-containing atomized nickel-iron powder to alkaline solution is 500-800 g / L; the alkaline solution is a sodium hydroxide solution with a mass concentration of 50%-70%; and the oxygen partial pressure is 1.5-3.5 MPa.

[0046] S5. The dealuminated intermediate powder is subjected to magnetic separation, dehydration and drying to obtain dealuminated atomized nickel-iron powder.

[0047] Magnetic separation refers to the preliminary separation of nickel-iron powder slurry using a wet magnetic separator to obtain wet nickel-iron powder with a moisture content of 25%-30%; dehydration refers to the dehydration treatment of the wet nickel-iron powder obtained by magnetic separation using a filter press to obtain wet nickel-iron powder with a moisture content of 10%-15%; drying refers to drying at 100-120℃ to obtain aluminum-containing atomized nickel-iron powder.

[0048] The number of magnetic separations can be adjusted according to the actual situation. When multiple separations are required, the powder after the previous magnetic separation is mixed with water to make a slurry, and then magnetic separation is continued.

[0049] S6. The dealuminized atomized nickel-iron powder is subjected to secondary annealing to obtain atomized nickel-iron powder with refined grains.

[0050] Secondary annealing involves heating the dealuminized nickel-iron powder to 450-550°C at a heating rate of 5-10°C / min under a hydrogen atmosphere, holding it at that temperature for 30-90 minutes, and then cooling it to room temperature in the furnace.

[0051] In this invention, secondary annealing allows nickel-iron atoms to re-nucleate at structural defects generated during the dealumination process, further refining the new grains and achieving further refinement of the internal grains.

[0052] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0053] Example 1 This embodiment provides a finely grained atomized nickel-iron powder, the preparation method of which includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel and iron elements in a mass ratio of 10:90, with the total mass content of nickel and iron accounting for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into an intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 0.1μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 200g:1000kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1500℃, the magnetic induction intensity to 0.08T, the stirring frequency to 5Hz, and the stirring time to 5min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.0 mm, and the slit of the high-pressure water flow outlet is 0.2 mm. The water and the melt flow form an impact angle of 40°. Start the atomization and control the melt flow velocity of the atomization system to be 0.5 kg / s, the water pressure to be 1 MPa, the water temperature to be 40℃, and the water flow velocity at the outlet to be 80 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 25%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 10%; (7) Drying: Dry at 100℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 450°C at a rate of 5°C / min and held for 30 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 50% according to a solid-liquid ratio of 500g / L, and oxygen is introduced (oxygen partial pressure is 1.5MPa). The temperature is raised to 180°C and kept at a pressure of 1.5MPa for 3 hours to obtain dealuminized intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 25%; pure water is added to make pulp and wash according to a solid content of 500g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a water content of 10%; (12) Drying: Dry at 100℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 450°C at 5°C / min and held for 30 min. Then it is cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains.

[0054] Example 2 This embodiment provides a finely grained atomized nickel-iron powder, the preparation method of which includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 12:88, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 0.5μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 300g:1000kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1520℃, the magnetic induction intensity to 0.12T, the stirring frequency to 10Hz, and the stirring time to 10min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.1 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 42°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.6 kg / s, the water pressure is 2 MPa, the water temperature is 45℃, and the water flow velocity at the outlet is 90 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 12%; (7) Drying: Dry at 105℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 480°C at a rate of 6°C / min and held for 40 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 55% according to a solid-liquid ratio of 550g / L, and oxygen is introduced (oxygen partial pressure is 2Mpa). The temperature is raised to 190°C and kept at a pressure of 2.0MPa for 3.5h to obtain dealuminized intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; pure water is added to make pulp and wash according to a solid content of 550g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a water content of 12%; (12) Drying: Dry at 105℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 480°C at a rate of 6°C / min and held for 40 min. It is then cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains. Please refer to [link to relevant documentation]. Figure 1 ,from Figure 1 It can be seen that nickel-iron powder was successfully prepared in this embodiment.

[0055] Example 3 This embodiment provides a finely grained atomized nickel-iron powder, the preparation method of which includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 15:85, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 1.0 μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 400 g: 1000 kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1550℃, the magnetic induction intensity to 0.14T, the stirring frequency to 12Hz, and the stirring time to 12min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.3 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 45°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 3 MPa, the water temperature is 50℃, and the water flow outlet velocity is 115 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (7) Drying: Dry at 110℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 500°C at 8°C / min and held for 60 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 60% according to a solid-liquid ratio of 650g / L. Oxygen is introduced (oxygen partial pressure is 2.5MPa) and the temperature is raised to 200°C. The solution is kept at a pressure of 2.5MPa for 4.5h to obtain dealuminized intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; pure water is added to make pulp and wash according to a solid content of 650g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (12) Drying: Dry at 110℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 500°C at a rate of 8°C / min and held for 60 min. It is then cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains. Please refer to [link to relevant documentation]. Figure 2 ,from Figure 2 It can be seen that nickel-iron powder was successfully prepared in this embodiment.

[0056] Example 4 This embodiment provides a finely grained atomized nickel-iron powder, the preparation method of which includes the following steps: (1) Smelting: The nickel-iron alloy blocks (with a nickel-iron element mass ratio of 50:50 and a total mass content of nickel and iron accounting for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into an intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 1.5μm to the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 500g:1000kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1580℃, the magnetic induction intensity to 0.18T, the stirring frequency to 15Hz, and the stirring time to 15min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.4 mm, and the slit of the high-pressure water flow outlet is 0.4 mm. The water and the melt flow form an impact angle of 48°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 4 MPa, the water temperature is 55℃, and the water flow velocity at the outlet is 130 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 25%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 10%; (7) Drying: Dry at 115℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 520°C at a rate of 9°C / min and held for 75 min, then cooled to 200°C in the furnace. (9) Dealumination: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 65% according to a solid-liquid ratio of 700g / L, and oxygen is introduced (oxygen partial pressure is 3Mpa) to raise the temperature to 210°C. Under the condition of 3.0MPa pressure, the powder is kept at the temperature for 5 hours to obtain dealumination intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 25%; pure water is added to make pulp and wash according to a solid content of 700g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a water content of 10%; (12) Drying: Dry at 115℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 520°C at 9°C / min and held for 75 min. It is then cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains.

[0057] Example 5 This embodiment provides a finely grained atomized nickel-iron powder, the preparation method of which includes the following steps: (1) Smelting: The nickel-iron alloy blocks (with a nickel to iron element mass ratio of 85:15 and a total mass content of nickel and iron accounting for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into an intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 2.0μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 600g:1000kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1600℃, the magnetic induction intensity to 0.20T, the stirring frequency to 20Hz, and the stirring time to 20min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.5 mm, and the slit of the high-pressure water flow outlet is 0.5 mm. The water and the melt flow form an impact angle of 50°. Start the atomization and control the melt flow rate of the atomization system to be 1.0 kg / s, the water pressure to be 5 MPa, the water temperature to be 60 ℃, and the water flow outlet velocity to be 150 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 30%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 15%; (7) Drying: Dry at 120℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 550°C at a rate of 10°C / min and held for 90 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 70% according to a solid-liquid ratio of 800g / L, and oxygen is introduced (oxygen partial pressure is 3.5Mpa) and the temperature is raised to 220°C. The solution is kept at a pressure of 3.5MPa for 6 hours to obtain dealuminized intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 30%; pure water is added to make pulp and wash according to a solid content of 800g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a water content of 15%; (12) Drying: Dry at 120°C to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 550°C at a rate of 10°C / min and held for 90 min. It is then cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains.

[0058] Comparative Example 1 This comparative example is basically the same as Example 3, except that (2) is not performed, that is, aluminum oxide is not added. In order to maintain consistency with the steps of Example 3, the dealuminization step of step (9) is retained.

[0059] A method for preparing finely grained atomized nickel-iron powder includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 15:85, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Omitted; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1550℃, the magnetic induction intensity to 0.14T, the stirring frequency to 12Hz, and the stirring time to 12min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.3 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 45°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 3 MPa, the water temperature is 50℃, and the water flow outlet velocity is 115 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (7) Drying: Dry at 110℃ to obtain preliminary atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the atomized nickel-iron powder is heated to 500°C at a rate of 8°C / min and held for 60 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 60% according to a solid-liquid ratio of 650g / L, and oxygen is introduced (oxygen partial pressure is 2.5Mpa) to raise the temperature to 200°C. The solution is kept at a pressure of 2.5MPa for 4.5h to obtain dealuminized intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; pure water is added to make pulp and wash according to a solid content of 650g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (12) Drying: Dry at 110℃ to obtain atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the atomized nickel-iron powder is heated to 500°C at 8°C / min and held for 60 min. Then it is cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains.

[0060] Comparative Example 2 This comparative example is basically the same as Example 3, except that the annealing in step (8) is not performed.

[0061] A method for preparing finely grained atomized nickel-iron powder includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 15:85, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 1.0 μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 400 g: 1000 kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1550℃, the magnetic induction intensity to 0.14T, the stirring frequency to 12Hz, and the stirring time to 12min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.3 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 45°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 3 MPa, the water temperature is 50℃, and the water flow outlet velocity is 115 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (7) Drying: Dry at 110℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing omitted; (9) Dealuminization: Add aluminum-containing atomized nickel-iron powder to a sodium hydroxide solution with a mass concentration of 60% according to a solid-liquid ratio of 650g / L, and introduce oxygen (oxygen partial pressure of 2.5Mpa) to raise the temperature to 200℃ and keep it at a pressure of 2.5MPa for 4.5h to obtain dealuminized intermediate powder; (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; pure water is added to make pulp and wash according to a solid content of 650g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (12) Drying: Dry at 110℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 500°C at 8°C / min and held for 60 min. It is then cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains.

[0062] Comparative Example 3 This comparative example is basically the same as Example 3, except that the oxygen in step (9) is replaced with nitrogen.

[0063] A method for preparing finely grained atomized nickel-iron powder includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 15:85, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 1.0 μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 400 g: 1000 kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1550℃, the magnetic induction intensity to 0.14T, the stirring frequency to 12Hz, and the stirring time to 12min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.3 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 45°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 3 MPa, the water temperature is 50℃, and the water flow outlet velocity is 115 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (7) Drying: Dry at 110℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 500°C at 8°C / min and held for 60 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 60% according to a solid-liquid ratio of 650g / L. Nitrogen gas (nitrogen partial pressure of 2.5MPa) is introduced and the temperature is raised to 200°C and the temperature is kept at 2.5MPa for 4.5h to obtain dealuminized intermediate powder; (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; pure water is added to make pulp and wash according to a solid content of 650g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (12) Drying: Dry at 110℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: Under a hydrogen atmosphere, the dealuminized atomized nickel-iron powder is heated to 500°C at 8°C / min and held for 60 min. It is then cooled to room temperature in the furnace to obtain atomized nickel-iron powder with refined grains.

[0064] Comparative Example 4 This comparative example is basically the same as Example 3, except that step (13) is not performed.

[0065] A method for preparing finely grained atomized nickel-iron powder includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 15:85, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Feeding: Add α-type alumina with a particle size Dv50 of 1.0 μm into the intermediate ladle according to the mass ratio of alumina to nickel-iron liquid of 400 g: 1000 kg; (3) Mixing: Start the tundish rotating electromagnetic stirrer, and control the tundish temperature to 1550℃, the magnetic induction intensity to 0.14T, the stirring frequency to 12Hz, and the stirring time to 12min to obtain a mixed melt; (4) Atomization: The mixed melt enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.3 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 45°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 3 MPa, the water temperature is 50℃, and the water flow outlet velocity is 115 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (7) Drying: Dry at 110℃ to obtain aluminum-containing atomized nickel-iron powder; (8) Annealing: Under a hydrogen atmosphere, the aluminum-containing atomized nickel-iron powder is heated to 500°C at 8°C / min and held for 60 min, then cooled to 200°C in the furnace. (9) Dealuminization: When the furnace is cooled to 200°C, aluminum-containing atomized nickel-iron powder is added to a sodium hydroxide solution with a mass concentration of 60% according to a solid-liquid ratio of 650g / L. Oxygen is introduced to raise the temperature to 200°C and the solution is kept at a pressure of 2.5MPa for 4.5h to obtain dealuminized intermediate powder. (10) Magnetic separation: The intermediate powder of dealuminization is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; pure water is added to make pulp and wash according to a solid content of 650g / L, and then a second magnetic separation is performed. (11) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (12) Drying: Dry at 110℃ to obtain dealuminized atomized nickel-iron powder; (13) Secondary annealing: omitted.

[0066] Comparative Example 5 This comparative example is basically the same as Example 3, except that steps (2) and (8)-(13) are not performed.

[0067] A method for preparing finely grained atomized nickel-iron powder includes the following steps: (1) Smelting: The nickel-iron alloy blocks (nickel to iron element mass ratio of 15:85, and the total mass content of nickel and iron accounts for more than 95% of the total metal mass content in the nickel-iron alloy blocks) from the pyrometallurgical smelting of laterite nickel ore are melted into nickel-iron molten liquid and poured into the intermediate ladle; (2) Add ingredients; omitted.

[0068] (3) Mixing: Start the intermediate batch rotating electromagnetic stirrer, and control the intermediate batch temperature to 1550℃, the magnetic induction intensity to 0.14T, the stirring frequency to 12Hz, and the stirring time to 12min; (4) Atomization: The molten nickel-iron enters the atomization system from the tundish. In the atomization system, a coaxial annular slit nozzle is used. The annular slit is the outlet of the high-pressure water flow, and the inner hole is the outlet of the melt flow. The outlet diameter of the melt flow is 1.3 mm, and the slit of the high-pressure water flow outlet is 0.3 mm. The water and the melt flow form an impact angle of 45°. Atomization is started, and the melt flow velocity of the atomization system is controlled at 0.8 kg / s, the water pressure is 3 MPa, the water temperature is 50℃, and the water flow velocity at the outlet is 115 m / s to obtain nickel-iron slurry. (5) Magnetic separation: The slurry is initially separated by a wet magnetic separator to obtain wet nickel-iron powder with a water content of 28%; (6) Dehydration: The wet nickel-iron powder obtained by magnetic separation is dehydrated by a vacuum filter to obtain wet nickel-iron powder with a moisture content of 13%; (7) Drying: Dry at 110°C to obtain atomized nickel-iron powder.

[0069] Comparative Example 6 This comparative example is basically the same as Example 3, except that the dealuminization step (9) of Example 3 is omitted in this comparative example.

[0070] Comparative Example 7 This comparative example is basically the same as Example 3, except that the alumina in Example 3 is replaced with aluminum hydroxide and the particle size is 0.05 μm.

[0071] Experimental Example 1 The nickel-iron powders obtained in Examples 1-5 and Comparative Examples 1-7 were tested, and the test results are shown in the table below: (1) The XRD pattern was tested using an Ultima IV X-ray diffractometer. The XRD test conditions were as follows: the Ultima IV series X-ray diffractometer was used, the X-ray source was Cu Kα rays with a wavelength of 1.5406 Å, the tube voltage was 40 kV, and the tube current was 40 mA; the scanning speed was 4° / min, and the scanning range 2θ was 10°-100°. The full width at half maximum (FWHM) and Bragg angle of the strongest diffraction peak were obtained, and the FWHM of the diffraction peak was converted to radians. The average grain size D was calculated using the following formula: D = The calculations were performed, where K = 0.89 and λ = 0.15406 nm; (2) The true density was tested using the Bestar Physical Adsorption Analyzer-TD; (3) The specific surface area was tested using a physical adsorption analyzer (Mc2460); (4) According to the powder activity H= Calculate the activity H of the powder.

[0072] Please refer to Table 1 for the test results: Table 1. Statistical table of physicochemical index test results of different examples of nickel-iron powder

[0073] As can be seen from the table above, in Comparative Example 1, without the participation of alumina, the nickel-iron molten metal could not form a large number of crystal nuclei during solidification, resulting in coarse grains. Although low-temperature annealing could promote recrystallization and homogenization, transforming coarse grains into finer grains, the absence of alumina to prevent grain boundary migration meant that the grains still grew, leading to a significantly larger average grain size D than in Example 3. When the average grain size D was outside the scope of this application, its powder activity H was significantly lower than in Example 3. In Comparative Example 2, due to the lack of low-temperature annealing, coarse grains still existed, resulting in a significantly larger average grain size D than in Example 3. In Comparative Example 3, replacing oxygen with nitrogen led to an increase in average grain size and a significant decrease in powder activity H. In Comparative Example 4, the nickel-iron powder exhibited slight oxidation, resulting in relatively coarse internal grains and a significantly larger average grain size D compared to Example 3. In Comparative Example 5, the absence of alumina induced the formation of numerous crystal nuclei during solidification of the molten nickel-iron, resulting in coarse grains. The lack of low-temperature annealing meant the coarse grains persisted, leading to the coarsest overall grain size, with an average grain size D significantly larger than Example 3 and other comparative examples. In Comparative Example 6, the nickel-iron powder contained aluminum, and although it was not oxidized, subsequent annealing and reduction resulted in relatively coarse grains. In Comparative Example 7, aluminum hydroxide dehydrated and agglomerated to form slag, a result largely consistent with Comparative Example 1 without alumina. From the above comparative examples, it can be seen that only when the average grain size D, specific surface area S, and true density ρ are all within the range of this application do they exhibit superior powder activity H. Conversely, when the average grain size D is outside the range of this application, even if the specific surface area S and true density ρ are within the range, superior powder activity H cannot be obtained. The powder activity H of the above comparative examples is significantly lower than that of Example 3.

[0074] Experimental Example 2 The nickel-iron powders obtained in Examples 1-5 and Comparative Examples 1-7 were acid-dissolved and their nickel-iron content was detected. The detection method included: placing 4.0g of nickel-iron powder in a beaker, adding 40mL of 2.0mol / L sulfuric acid, reacting in a water bath at 25℃ for 20min, taking the supernatant, and testing the nickel and iron content using the standard GB / T 30902-2014 Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) for the determination of impurity elements in inorganic chemical products.

[0075] Please refer to Table 2 for the test results:

[0076] As can be seen from the table above, the powder in the embodiment of the present invention has high activity, and the corresponding nickel and iron leaching contents are significantly higher than those in the comparative example. It has a good acid dissolution rate in the subsequent acid dissolution process and the leached nickel and iron contents are high.

[0077] In summary, the grain-refined atomized nickel-iron powder provided by this invention has a large specific surface area and fine grains, thus exhibiting a good acid dissolution rate and high nickel-iron content during subsequent acid dissolution. This invention also provides a method for preparing the aforementioned grain-refined atomized nickel-iron powder. By adding alumina as a grain refiner, which has a high melting point and can stably exist in a high-temperature mixed melt, it acts as a non-uniform nucleation core during water atomization, pinning and inducing the formation of numerous crystal nuclei in the nickel-iron mixture during solidification, forcing the grains to become finer. During annealing, heating and slowly cooling the aluminum-containing atomized nickel-iron powder promotes recrystallization and homogenization, transforming coarse grains into fine ones. Simultaneously, the pre-distribution of alumina on the grain boundaries prevents grain boundary migration, further inhibiting high-temperature grain growth. During dealumination, an alkaline solution is used to dissolve and remove α-alumina. However, the presence of oxygen in the alkaline solution causes slight oxidation of the nickel-iron powder, resulting in numerous structural defects. Through secondary annealing and reduction, nickel-iron atoms re-nucleate at the defects, the newly formed grains are further refined, and the internal grains are further refined, ultimately obtaining atomized nickel-iron powder with a large specific surface area and fine grains.

[0078] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A finely grained atomized nickel-iron powder, characterized in that, X-ray diffraction analysis showed that the average grain size D perpendicular to the measured crystal plane was 18-25 nm, and the average grain size D was calculated using the Scherrer formula: D = ... calculate; K is the shape factor, a constant, and is set to 0.89; λ is the X-ray wavelength, λ = 0.15406 nm; β is the full width at half maximum (FWHM) of the diffraction peak, in radians; θ is the Bragg diffraction angle, expressed in degrees.

2. The atomized nickel-iron powder with refined grains according to claim 1, characterized in that, The specific surface area S of the finely grained atomized nickel-iron powder is 0.5-2.5 m². 2 / g; and / or, the true density ρ of the grain-refined atomized nickel-iron powder is 7.6-8.7 g / cm³. 3 .

3. The finely grained atomized nickel-iron powder according to claim 2, characterized in that, The powder activity H of the finely grained atomized nickel-iron powder is... The powder activity H of the finely grained atomized nickel-iron powder is 7-22 m / g.

4. A method for preparing atomized nickel-iron powder with refined grains as described in any one of claims 1-3, characterized in that, It includes: Alumina is added to molten nickel-iron and mixed thoroughly to obtain a mixed melt; The mixed melt is atomized by high-pressure water to obtain nickel-iron powder slurry; The nickel-iron powder slurry is subjected to magnetic separation, dehydration and drying to obtain aluminum-containing atomized nickel-iron powder; The aluminum-containing atomized nickel-iron powder is annealed and then placed in an alkaline solution to remove aluminum, resulting in a dealuminized intermediate powder. The dealuminated intermediate powder is subjected to magnetic separation, dehydration and drying to obtain dealuminated atomized nickel-iron powder; The dealuminated nickel-iron powder is subjected to secondary annealing to obtain atomized nickel-iron powder with refined grains.

5. The method for preparing finely grained atomized nickel-iron powder according to claim 4, characterized in that, The alumina is α-type alumina with a particle size Dv50 of 0.1-2.0 μm; And / or, the mass ratio of the alumina to the molten nickel-iron is (200g-600g):1000kg.

6. The method for preparing grain-refined atomized nickel-iron powder according to claim 4, characterized in that, The annealing process includes heating the aluminum-containing atomized nickel-iron powder to 450-550°C at a heating rate of 5-10°C / min under a hydrogen atmosphere, holding it at that temperature for 30-90min, and then cooling it to 180-220°C in the furnace. And / or, the dealuminization includes adding the annealed and furnace-cooled aluminum-containing atomized nickel-iron powder to an alkaline solution, introducing oxygen, and soaking it for 3-6 hours at a temperature of 180-220°C and a pressure of 1.5-3.5 MPa.

7. The method for preparing finely grained atomized nickel-iron powder according to claim 6, characterized in that, The solid-liquid ratio of the aluminum-containing atomized nickel-iron powder to the alkaline solution is 500-800 g / L; And / or, the alkaline solution is a sodium hydroxide solution with a mass percentage concentration of 50%-70%; And / or, the oxygen partial pressure of the oxygen is 1.5-3.5 MPa.

8. The method for preparing grain-refined atomized nickel-iron powder according to claim 4, characterized in that, The secondary annealing includes heating the dealuminized nickel-iron powder to 450-550°C at a heating rate of 5-10°C / min under a hydrogen atmosphere, holding it at that temperature for 30-90 minutes, and then cooling it to room temperature in the furnace.

9. The method for preparing finely grained atomized nickel-iron powder according to claim 4, characterized in that, The mixing process includes rotating the molten nickel-iron and the alumina using electromagnetic stirring. The magnetic induction intensity of the electromagnetic stirring is 0.08-0.20T, the stirring frequency is 5-20Hz, the stirring time is 5-20min, and the stirring temperature is 1500℃-1600℃.

10. The method for preparing finely grained atomized nickel-iron powder according to claim 4, characterized in that, During high-pressure water atomization, the flow rate of the mixed melt is 0.5-1.0 kg / s, the water pressure is 1-5 MPa, the water temperature is 40-60℃, and the water flow rate is 80-150 m / s. And / or, the high-pressure water atomization is performed using a coaxial annular slit nozzle, wherein the annular slit is the high-pressure water outlet and the inner hole is the melt outlet; the diameter of the melt outlet is 1.0-1.5mm, the slit of the high-pressure water outlet is 0.2-0.5mm, and the water and the melt flow form an impact angle of 40°-50°.